An ungovernable anarchy: The United States' response to depression and default, 1837 - 1848 - Alasdair Roberts (Intereconomics, 2010)
American commentators have criticized European leaders for failing to deal firmly and swiftly with the eurozone's sovereign debt crisis. These commentators forget the lessons of American history. The United States experienced a similar crisis following the financial panic of 1837. Eight states defaulted and political turmoil intensified, undermining stability in several states and the federal system itself. The restoration of economic and political order was a prolonged and painful process, as enraged voters confronted the costs of inaction and accepted new constraints on democratic processes. Will the European crisis play out similarly?
Keywords: 330